2017
DOI: 10.1039/c7ra10148a
|View full text |Cite
|
Sign up to set email alerts
|

Restorable, high-strength poly(N-isopropylacrylamide) hydrogels constructed through chitosan-based dual macro-cross-linkers with rapid response to temperature jumps

Abstract: Thermo-responsive, high mechanical poly(N-isopropylacrylamide) hydrogels with excellent recoverability and rapid response rate are constructed on chitosan-based dual macro-cross-linkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
1
10
0
1
Order By: Relevance
“…Normalized swelling and deswelling rates of the 10 °C sample were calculated by dividing the volume change rates obtained from Figure 3d by the swollen hydrogel volume, then compared to those calculated from some representative literature focusing on fast stimuli-responsive PNIPAM hydrogels (Figure 3e). [46][47][48][49][50][51][52][53][54][55][56][57][58][59] In this comparison, it is readily observed that both normalized swelling and deswelling rates in this work are about an order of magnitude higher than what has been reported. Comparing to the few works measuring both the deswelling rate and Young's modulus of their PNIPAM hydrogels, this work demonstrates a record-breaking order of magnitude improvement in both properties without compromise (Figure 3f).…”
Section: Resultsmentioning
confidence: 66%
“…Normalized swelling and deswelling rates of the 10 °C sample were calculated by dividing the volume change rates obtained from Figure 3d by the swollen hydrogel volume, then compared to those calculated from some representative literature focusing on fast stimuli-responsive PNIPAM hydrogels (Figure 3e). [46][47][48][49][50][51][52][53][54][55][56][57][58][59] In this comparison, it is readily observed that both normalized swelling and deswelling rates in this work are about an order of magnitude higher than what has been reported. Comparing to the few works measuring both the deswelling rate and Young's modulus of their PNIPAM hydrogels, this work demonstrates a record-breaking order of magnitude improvement in both properties without compromise (Figure 3f).…”
Section: Resultsmentioning
confidence: 66%
“…Thermoresponsive Cs-g-PNIPAAm hydrogels are typically synthesized via ceric ammonium nitrate [49] or 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide [50]. However, grafting can be problematic with a narrow distribution of molecular weight on the side chains.…”
Section: Discussionmentioning
confidence: 99%
“…; limiting the preparation technique’s usage [ 129 ]. Several investigations have been reported e.g., alginate/ N -isopropylacrylamide (NIPAM) hydrogel [ 131 ], PNIPAM/poly(sodium acrylate) hydrogel [ 132 ], methacryloylchitosan/PNIPAM hydrogel [ 133 ], polyacrylamide/sodium alginate IPN hydrogel [ 134 ], etc. ; based on ionic interaction of PNIPAM-based hydrogel systems for improving stiffness, cell viability, and mechanical integrity of the hydrogel system.…”
Section: Preparation Of Pnipam-based Hydrogel Systemsmentioning
confidence: 99%